A case of infective endocarditis and pyogenic spondylitis after transrectal ultrasound guided prostate biopsy. Issue 11 (November 2016) - Hiyama, Yoshiki; Takahashi, Satoshi; Uehara, Teruhisa; Ichihara, Koji; Hashimoto, Jiro; Masumori, Naoya
Abstract: We report a patient with infective endocarditis and pyrogenic spondylitis occurring simultaneously. The patient was a 59-year-old man. He was suspected of having prostate cancer due to a high prostate-specific antigen concentration noted in a checkup. He then underwent a transrectal ultrasound guided prostate biopsy with cefotiam as antimicrobial prophylaxis. He had a fever higher than 38 °C and lumbar pain for a few days after the biopsy. Enterococcus faecalis was isolated from 2 sets of blood culture. Magnetic resonance imaging revealed an abnormal image at C7/Th1 with a signal decrease in T1-weighted sequences and signal increase in T2-weighted sequences that were suspected to be due to bone destruction. Therefore, he was diagnosed as having pyogenic spondylitis by an orthopedist. At the same time, he complained of palpitation and a heart murmur was detected. Then transesophageal echocardiography was performed by a cardiologist and it revealed vegetation in his left ventricle and aortic regurgitation, and finally acute cardiac insufficiency was determined. He was treated with tazobactam/piperacillin and aortic valve displacement surgery. Based on the results of the prostate biopsy and image inspection, he was diagnosed as having localized prostate cancer. He was treated by androgen deprivation therapy and external beam radiation therapy. We have to keep in mind that E. faecalis can be a potential pathogen for severe infectious complications after prostate biopsy, especially if a cephalosporin is selected for antimicrobial prophylaxis.